1992
DOI: 10.1002/lsm.1900120515
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of lupus pernio with the flashlamp pulsed dye laser

Abstract: Lupus pernio, a form of cutaneous sarcoidosis usually affecting the face, is often disfiguring and resistant to therapies, both medical and surgical. To our knowledge, there have been no previous reports of laser therapy for this condition. We describe a case of nasal lupus pernio successfully managed with the flashlamp pulsed dye laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…146 Evidence supporting the efficacy of these medications is scant. Case studies have reported therapeutic benefit for psoralen plus ultraviolet A light phototherapy, 147,148 photodynamic therapy, [149][150][151] pulsed-dye lasers, 152 and CO 2 lasers. 153 The surgical resection of sarcoidal lesions is rarely performed.…”
Section: Therapymentioning
confidence: 98%
“…146 Evidence supporting the efficacy of these medications is scant. Case studies have reported therapeutic benefit for psoralen plus ultraviolet A light phototherapy, 147,148 photodynamic therapy, [149][150][151] pulsed-dye lasers, 152 and CO 2 lasers. 153 The surgical resection of sarcoidal lesions is rarely performed.…”
Section: Therapymentioning
confidence: 98%
“…Goodmann et al also described a clear improvement of the skin findings of lupus pernio of the nose using a pulsed dye laser [19]. In this instance, the remission was largely attributed to the immunomodulatory effect of the dye laser, which corresponded to the theory postulated by Alster et al in 1997 [20].…”
Section: Discussionmentioning
confidence: 57%
“…9,10 Plastic surgery and flashlamp pulsed dye laser therapy for the lesions of lupus pernio have been reported with some success, but these are not usual therapies for sarcoid in that they may cause additional disfigurement, and treat locally a disease that may be a more widespread process. 11,12 Nonsteroidal antiinflammatory medications and potassium iodide have been effective for diminishing the symptoms and hastening the resolution of erythema nodosum associated with sarcoid, but have not been useful in other forms of cutaneous sarcoid. 4 Thalidomide has been used with some success and appears to be a promising therapy because of its immune-modulating effect.…”
Section: Discussionmentioning
confidence: 99%